Old Tales for a New Gens. Alberic of Trois-Fontaines’ Grafting of History - Grabowski, Antoni (Acta Poloniae Historica, 2022)
Throughout the Middle Ages, waves of people came to the lands once been a part of the Roman Empire. At the same time, lands yet unknown encountered the successors of the Empire. These gentes sometimes preserved a long history of their paths to their new homelands. The Longobards, the Saxons, and many others had an origo gentis, where gods played an important role. These narrations were incorporated into a historiography that was almost entirely Christian. This article is concerned with the methods used to find harmony between the past and present by Alberic of Trois-Fontaines when writing about the Semigallians. The narrative of their origins used established motifs and themes that made it possible to include the invented history of the gens into the then-established universal history. This was done through the etymology of names or the erudite use of the writings of other authors. These new gentes were grafted onto the trees of old tales.